EDUKASI MASYARAKAT SULIT AIR MENUJU PERTANIAN ORGANIK MELALUI INTRODUKSI PESTISIDA ALAMI DAN PUPUK ORGANIK CAIR - Renny Eka Putri; Najeli Rahmatika; Dhiya Ulwafi; Roy Saputra; Roni Andika Putra; Joko Prastio; Shakira Azzura Syaidev; Elfy Adelliana; Sherly Rahmadenita (Jurnal Hilirisasi IPTEKS, 2023)
Nagari Sulit Air is one of the villages in the administrative area of Solok Regency, West Sumatra province where agriculture plays an important role in the economy of the Nagari Sulit Air community. Geographically, Nagari Sulit Air is located in a highland area with fertile land topography. This is well utilized by the community, by making agriculture the main commodity. The crops generally grown by the community are horticultural crops such as rice, chilies and dragon fruit which are the main agricultural commodities. Even for dragon fruit, Nagari Sulit Air is one of the central areas in Solok Regency. Because the potential is quite promising, there are many chemical fertilizer products circulating in the community. The purpose of this activity is to increase the knowledge of Nagari Sulit Air farmers about the benefits of liquid organic fertilizers and vegetable pesticides and increase farmers' skills in making organic fertilizers. The method used is the Counseling and Training method. Stages in counseling include planning, implementation and evaluation. The target of this activity is the community, especially farmer groups in Nagari Sulit Air. Educational and socialization activities regarding the manufacture of liquid organic fertilizers (POC) and vegetable pesticides can increase the knowledge of farmers in Nagari Sulit Air. And it can also be used as a solution to increase the production and quality of agricultural products in Nagari Sulit Air. The realization of the application of organic farming in Nagari Sulit Air requires support from all relevant stakeholders.